Sembrando - Suka Fiszman, Nicolás (2011)
El autor reseña la formación académica y la carrera profesional de los integrantes del estudio.
Keywords: ESTUDIO BORRACHIA; BORRACHIA, OSCAR A; BORRACHIA, ALEJANDRO H; ARGENTINA; ARQUITECTURA; ESTUDIOS DE ARQUITECTURA